2020
DOI: 10.1159/000505936
|View full text |Cite
|
Sign up to set email alerts
|

Primary Mediastinal Seminoma Achieved by Transbronchial Mediastinal Cryobiopsy

Abstract: Mediastinal biopsy is essential for the clinical diagnosis of mediastinal disease. Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is a well-established approach for obtaining diagnostic samples from mediastinal masses or enlarged lymph nodes which is proven to be minimally invasive and effective. However, the insufficiency of intact samples acquired might restrict the diagnostic efficacy of EBUS-TBNA for mediastinal lesions such as rare malignancy and granulomatous disorder. We he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 10 publications
1
26
0
2
Order By: Relevance
“…Zhang et al have reported a case of EBUS‐guided transbronchial mediastinal cryo‐biopsy where the advantages of cryo‐biopsy and EBUS were combined [13]. In this report, the author has performed transbronchial cryo‐biopsy in a similar technique as ours, except using a high‐frequency cautery needle knife to create an entry site for the cryo‐probe.…”
Section: Discussionmentioning
confidence: 92%
“…Zhang et al have reported a case of EBUS‐guided transbronchial mediastinal cryo‐biopsy where the advantages of cryo‐biopsy and EBUS were combined [13]. In this report, the author has performed transbronchial cryo‐biopsy in a similar technique as ours, except using a high‐frequency cautery needle knife to create an entry site for the cryo‐probe.…”
Section: Discussionmentioning
confidence: 92%
“…In all of these five cases, there was no report of any evident complications related to the cryobiopsy procedure. 7,8 In the first prospective randomized study, Zhang et al 9 presented their experience in 197 cases comparing transcarinal cryobiopsy versus TBNA with EBUS visualization. The overall diagnostic yield was 79.9% and 91.8% for TBNA and transbronchial mediastinal cryobiopsy, respectively (p = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…A small number of case reports described a novel method of transcarinal cryobiopsy from mediastinal lymph nodes, 7,8 and recently a randomized clinical trial was published with impressive diagnostic results. 9 In this prospective pilot trial, we assessed the efficacy and safety of transcarinal EBUS-guided lymph node cryobiopsy, following EBUS-TBNA in 24 patients.…”
Section: Introductionmentioning
confidence: 99%
“…One such approach is the recently reported transbronchial mediastinal cryobiopsy. Recent studies support that cryobiopsy yields larger amounts of intact tissue and has improved diagnostic yield when compared with EBUS-TBNA [ 20 , 21 , 22 ]. However, how this new technique compares with the SonoTip TopGain ® needle has not been studied.…”
Section: Discussionmentioning
confidence: 99%